Bicycle Seat Cover Free Energy Generator - Mat Zian @ Mat Zin, Ahmad Faiz; Mantari,; M.H.A.R.,; NHINA,; N.H. Nizam,; M.H. Zainuden, (Multidisciplinary Applied Research and Innovation, 2023)
Bicycle Seat Cover Free Energy Generator is an energy generator using a piezoelectric main energy source. Piezoelectric materials can transform mechanical strain and vibration energy into electrical energy. This property allows opportunities for implementing renewable and sustainable energy power harvesting. This study is to design and develop a bicycle seat-free energy generator. Besides that, studying the stress contribution to piezoelectric can be achieved and to examine the interaction between the piezoelectric connection and its configuration in order to charge Li-Po batteries. The product development process involves mechanical component design using SolidWorks, material selection, fabrication, 3D printing manufacturing, assembly, and testing for result evaluation. From the testing implemented, the portable generator is capable of producing direct current voltages between 6 to 7 volts, as demonstrated by testing of its electrical performance. By using the solidworks@simulation, it will be possible to cut down on the amount of time required to study stresses, strains and safety factors, or component deformation analysis without first setting loads and boundary conditions. This is done so that the product may be generated more easily and without any complications, and so that the time spent analysing the data can be reduced.